(untitled) (International Journal on Stereo & Immersive Media, 2025)
This article discusses the design of the embodied installation game Sisyphus: Endless Dilemma, designed to help examine and resolve the inequalities faced by patients with mood disorders. By employing a critical design framework and the form of an interactive art installation, Sisyphus: Endless Dilemma creates a dystopian physical interactive environment to immerse players in an inescapable predicament to evoke empathy for mood disorder groups. This embodied installation game takes artistic research as an overarching method. Through the iterative creation of, and reflection upon, an experimental game within a performative context we aim to generate new knowledge on spatial and experimental game design. The resulting gameplay is not only shaped by a set of interaction mechanisms but also composed of elements such as various sensory experiences, bodily movements, and the physical environment. The article illustrates the potential of the embodied installation game based on artistic research in contributing to the discourse on contemporary game design as well as serving as a catalyst for addressing social issues, moral dilemmas and cultural challenges.